Implementasi Pelaksanaan Eksekusi Jaminan Fidusia Berdasarkan Putusan Mahkamah Konstitusi Nomor 18/Puu-Xvii/2019 Tentang Jaminan Fidusia (Studi Pada Koperasi Wahidiyah Ta’Awun Kepanjen Malang) - Amilatul, Siti Nur; Suciati, Suciati; Ambarsari, Ririen Indria Dian (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2021)
This study want to identify and analyze directly the implementation of the Constitutional Court Decision Number 18 / PUU-XVII / 2019 regarding the Fiduciary Guarantee Execution and to find out how the default settlement procedure in credit agreements in cooperatives with Fiduciary Guarantee and the obstacles faced in the process of executing fiduciary guarantees. This research is the result of field research field research, the formulation of the problem examined is how the fiduciary guarantee execution mechanism in the Constitutional Court decision No.18 / PUU-XVII / 2019 and how the implementation of fiduciary guarantee execution after the MK decision No.18 / PUU-XVII / 2019 at the Wahidiyah Ta'awun Union Kepanjen. Before the issuance of the Decision of the Constitutional Court Number 18 / PUU-XVII / 2019, the execution of guarantees for debtors who have defaulted is regulated under Articles 29 to Article 34 of Law Number 42 of 1999 concerning the Execution of Fiduciary Collateral. After the Constitutional Court Decision, the execution of fiduciary guarantees is carried out by negotiation and mutual agreement of the default, if there is no agreement between the Debtor and the Cooperative Management, then the applicable legal procedure must be carried out, namely a civil lawsuit in court.